DETECTION OF EARLY PREGNANCY IN AWASSI EWES BY MEASUREMENT OF BLOOD PROGESTERONE LEVELS - A. Fahmi, H.; A.R. Fathalla, M.; 0. Hussain , S. (The Iraqi Journal of Veterinary Medicine, 1989)
Twenty Awassi ewes aged 2-3 years were used in this experiment. Estrus was synchronized in these ewes by using intravaginal sponges containing 60 mg of Medroxy Progoesterone Acetate (MAP) which was kept for 9 days followed by intramuscular injection of 500 IU of Pregnant Mares Serum Gonadotrophin (PMSG) immediately after withdrawal of the sponges. Ewes were monitored for signs of estrus by means of an apronized detector ram, those which came into estrus were hand-mated to a known fertility rams. Following the service, blood was drawn from the jugular vein of each ewe at days 0 (before sevice), 12, 16,24,28,35,42 and 50. Serum was isolated and utilized for progesterone assay. Progesterone was assayed by RIA method. Mean progesterone concentrations for the fore mentioned periods were: 0.263, 4.909, 5.290, 5.21, 5.1, 5,18, 5.59 and 5.17 ng/ml, respectively. Mean progesterone concentration in ewes bearing single fetus for the above mentioned periods were: 3.64, 3.48, 3.78, 3.7, 3.84, and 3.74 ng/ml, respectively. While in those bearing twin were: 6.58, 6.58, 6.64, 6.7, 6.66, 7.34 and 6.6 ng/ml, respectively. The conclusion was that progesterone assay proved to be a reliable method for early detection of pregnancy in Awassi ewes and can be used to differentiate between single and twin pregnancies.